SELECTION OF AN IDEAL MESH SIZE FOR THE CRACKING UNIT OF A PALM KERNEL PROCESSING PLANT (Journal of Science and Technology, 2016)
One of the main problems associated with cracking of palm nut is the mixture of small Tenera and the big Dura variety nuts. In general, low yield of about 40% is obtained from cracking the mixture of Dura-Tenera nuts. In cracking the mixture, most of the Tenera nuts are not cracked when a large sieve size is used. When the sieve size is small, the Dura kernels get broken, thereby affecting the quality of the processed kernel oil. Hence the objective of this work was to develop a model for selecting a suitable sieve size that can be used to crack the nut in order to increase productivity and also improve the quality of the palm kernel oil. Series of experiments carried out confirmed the need for separation of nuts before cracking and also the need to select an ideal sieve size for each type of nut. In conclusion, it was established that separating the two nut varieties before cracking led to a significant (p< 0.01) increase in cracking efficiency of up to about 90% thereby increasing the productivity by 40% and making an economic gain of GH¢ 1.07 (US$0.98, October, 2008) per every 50 kg nut processed.